Synthesis of Fatty Hydroxamic Acids (FHAs) from Coconut Oil Using Lipase as a Catalyst - Henry Macandal (International Journal of Science and Society, 2019)
Fatty hydroxamic acids (FHAs) have been successfully synthesized from coconut oil by a one-step lipase catalyzed reaction. FHAs are the acids that are based on fatty acids. Their hydrophobicity can be use for some applications such as surfactant and metal ions extraction from aqueous media. This paper describes enzymatic synthesis of FHAs from coconut oil by reacting hydroxylamine with the substrate catalyzed by a lipase. The lipase used was Lipozyme, a commercially lipase of Mucor meihe fixed on a polymer anion exchange resin. The use of immobilized lipase as the catalyst for the preparation reaction provides an easy isolation of the enzyme from the products and other components in the reaction mixture. In addition, it also allows the reaction to be carried out under mild conditions, which reduces the reaction’s side products. The optimum preparation conditions obtained were as follows; the reaction temperature was 30oC, the reaction time was 30 h, the ratio of coconut oil: lipozyme (g:g) was 29.5, and the ratio of hydroxylamine: coconut oil (mmol:mmol) was 6. The solvent used was hexane. The purified products were characterized by qualitative test, such as FTIR spectroscopy and HPLC.